PELATIHAN DESIGN UI/UX DALAM MEMBANGUN WEBSITE PADA RW.013 CIPINANG MELAYU JAKARTA TIMUR - Lusa Indah Prahartiwi; Wulan Dari; Endang Pujiastuti; Yuyun Yuningsih (Jurnal AbdiMas Nusa Mandiri, 2023)
Rukun Warga is a community institution that was formed through deliberation of neighborhood association administrators in order to provide government services to the community that are recognized by the local government. However, along with the rapid development of information, the services provided by RW administrators. 013 Cipinang Melayu is still not optimal because it still uses a manual system. There is no information system to find out any information available in the RW area. 013 Cipinang Melayu is one of the obstacles in the field. Therefore, it is hoped that this web-based information system can reduce the risks faced by manual systems so that the services provided can be more effective and efficient. The results of this community service activity are in the form of a website-based community information system. By determining an attractive user interface/appearance of a website and the UX designer is tasked with determining how the website operates so as to produce an information system with a user interface that is effective for use. With this information system, it is hoped that it will make it easier for RW administrators and the public to collect data or obtain information.